Political Reposition of Authority in South Nias DPRD Members in 2014 Election (A Study on Social Construction of Peter L. Berger) - Hadirat Manao (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2020)
The establishment of South Nias Regency is of course accompanied by the formation of new legislative and executive institutions to run the government. The formation of these institutions provided an opportunity for the emergence of local Nias Selatan Elits to take up positions as legislators and regional heads. Reflecting from the above view, this research is a case study that focuses on developing in-depth descriptions and explanations of the meaning of the position of legislative members in South Nias in 2014. specifically the perspective of Peter L Berger's social construction. reality of the meaning of office is in the view of members of the South Nias DPRD, namely as a mandate, arena of contestation, and aspects of interests. The factors underlying the interest of South Nias DPRD members towards positions were formed in two spheres, namely the individual domain and the community domain. In the individual domain, their interest in the position is motivated by four factors, namely internal motivation, external motivation, skills, and goals. While in the community domain there are three factors, namely the previous orientation, current orientation, and future orientation.